The Complex World of Polysaccharides - Nedra Karunaratne, Desiree (IntechOpen, 2012)
The complex world of polysaccharides is a compilation of the characteristics of a variety of polysaccharides from plants, animals and microorganisms. The diversity of these polysaccharides arises from the structural variations and the monosaccharide content which is under genetic control. The chemical and physical properties have made them useful in many pharmaceutical, food and industrial applications. These properties of the polysaccharides determine their biological activity and their function in various applications. The role played by polysaccharides in preservation and protection of food, as carriers of nutrients and drugs, their ability to interact with molecules both for efficient delivery as well as improving textures of food colloids and their use as therapeutics are some of the functions discussed.